Your next breath - Johansen, Iris (New York : St. Martin's Press, 2015)
"Past is present. Catherine Ling has done everything she can to escape her past and create a new life, far from her rough beginnings. But someone has followed her trail and is playing a deadly game with her, using those she cares about as pawns."--Provided by publisher.
Keywords: Revenge -- Fiction; Suspense fiction